2021
DOI: 10.1039/d0py01311k
|View full text |Cite|
|
Sign up to set email alerts
|

Polymerization-induced self-assembly via RAFT in emulsion: effect of Z-group on the nucleation step

Abstract: Polymerization-Induced Self-Assembly (PISA) has emerged as one of the most powerful and widely employed techniques for preparation of block copolymer and polymeric nanoparticles in dispersed systems. Its success relies on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 50 publications
1
44
1
1
Order By: Relevance
“…Very large particle radii of 85 nm and 96 nm were synthesized for 35 wt% and 40 wt% as measured by DLS, when replacing the propyl Z-group with a butyl Z-group. These results fit to the proposed mechanism from Zetterlund et al, which was also shown in Figure 8 for hydrophilic RAFT agents [53]. However, the very large deviation of Mn,exp from Mn,theo infers a not well-controlled polymerization.…”
Section: The Synthesis Of Pmaa-b-ps With Cta2 Via Raft Emulsion Polymerizationsupporting
confidence: 88%
See 3 more Smart Citations
“…Very large particle radii of 85 nm and 96 nm were synthesized for 35 wt% and 40 wt% as measured by DLS, when replacing the propyl Z-group with a butyl Z-group. These results fit to the proposed mechanism from Zetterlund et al, which was also shown in Figure 8 for hydrophilic RAFT agents [53]. However, the very large deviation of Mn,exp from Mn,theo infers a not well-controlled polymerization.…”
Section: The Synthesis Of Pmaa-b-ps With Cta2 Via Raft Emulsion Polymerizationsupporting
confidence: 88%
“…In case of a hydrophilic RAFT agent, for example the CTA1 at very high solid concentrations of styrene (above 30 wt%), slow nucleation and polymerization occurs. The group of Zetterlund et al described that this phenomenon is caused by the Z-group induced RAFT exit [53]. The Z-group RAFT species is produced by the addition of a radical, entering a precursor particle and fragmentation afterwards to create a PMAA radical (pre-equilibrium of the RAFT mechanism, see Figure 9).…”
Section: Kinetics Of the Synthesis Of Pmaa-b-ps With Cta1 Via Raft Emulsion Polymerizatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of RAFT polymerization in dispersed systems provides access to numerous types of polymeric nanoparticles of complex internal structure and morphology, [3][4] most notably via Polymerization-Induced Self-Assembly (PISA). [5][6][7] One of the most important features of RDRP and RAFT is the ability to prepare a wide range of block copolymers. 8 Such polymers are of interest for a multitude of reasons, which include potential applications in e.g.…”
Section: Introductionmentioning
confidence: 99%